Application of the advance incision in robotic-assisted laparoscopic rectal anterior resection - Qiu, Yuhao; Li, Ying; Chen, Zhenzhou; Chai, Ninghui; Liang, Xianping; Zhang, Dahong; Wei, Zhengqiang (Frontiers in Surgery, 2023)
Background The incidence of rectal cancer is increasing each year. Robotic surgery is being used more frequently in the surgical treatment of rectal cancer; however, several problems associated with robotic surgery persist, such as docking the robot repeatedly to perform auxiliary incisions and difficulty exposing the operative field of obese patients. Herein we introduce a new technology that effectively improves the operability and convenience of robotic rectal surgery. Objectives To simplify the surgical procedure, enhance operability, and improve healing of the surgical incision, we developed an advance incision (AI) technique for robotic-assisted laparoscopic rectal anterior resection, and compared its safety and feasibility with those of intraoperative incision. Methods Between January 2016 and October 2021, 102 patients with rectal cancer underwent robotic-assisted laparoscopic rectal anterior resection with an AI or intraoperative incision (iOI) incisions. We compared the perioperative, incisional, and oncologic outcomes between groups. Results No significant differences in the operating time, blood loss, time to first passage of flatus, time to first passage of stool, duration of hospitalization, and rate of overall postoperative complications were observed between groups. The mean time to perform auxiliary incisions was shorter in the AI group than in the iOI group (14.14 vs. 19.77 min; p < 0.05). The average incision length was shorter in the AI group than in the iOI group (6.12 vs. 7.29 cm; p < 0.05). Postoperative incision pain (visual analogue scale) was lower in the AI group than in the iOI group (2.5 vs. 2.9 p = 0.048). No significant differences in incision infection, incision hematoma, incision healing time, and long-term incision complications, including incision hernia and intestinal obstruction, were observed between groups. The recurrence (AI group vs. iOI group = 4.0% vs. 5.77%) and metastasis rates (AI group vs. iOI group = 6.0% vs. 5.77%) of cancer were similar between groups. Conclusion The advance incision is a safe and effective technique for robotic-assisted laparoscopic rectal anterior resection, which simplifies the surgical procedure, enhances operability, and improves healing of the surgical incision.